Study on the deposition and tribological properties of diamond/DLC composite coating on WC-Co substrate. (1st January 2013) - Shen, Bin; Wang, Liang; Chen, Sulin; Sun, Fanghong
Two types of diamond/DLC composite films, namely MCD/DLC and NCD/DLC, are fabricated on the WC-Co substrate by depositing a layer of DLC film on the surface of conventional MCD and NCD film. Characterisations on their surface morphology suggest that the diamond/DLC composite films exhibit a rather similar surface topography, but much lower surface roughness, comparing with the single-layered MCD or NCD film. The atomic-bonding state on their surface is largely determined by the top-layered DLC film, which is mainly composed of amorphous carbon phase. The results of friction tests indicate that the self-lubricating effect of top-layered DLC film significantly suppresses the initial friction peak and shortens the run-in period. With silicon nitride as the counterpart material, the average friction coefficients of MCD/DLC and NCD/DLC composite films during stable sliding period are respectively 0.07 and 0.10 in dry sliding, and 0.03 and 0.07 under water-lubricating condition.